The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1093/jnci/djs433
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness Analysis of Screening for KRAS and BRAF Mutations in Metastatic Colorectal Cancer

Abstract: Screening for KRAS and BFAF mutation improves the cost-effectiveness of anti-EGFR therapy, but the incremental cost effectiveness ratio remains above the generally accepted threshold for acceptable cost effectiveness ratio of $100 000/quality adjusted life year.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
107
1
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(109 citation statements)
references
References 52 publications
0
107
1
1
Order By: Relevance
“…Of the remaining 29 titles, the full papers were screened, which led us to exclude another 24, leaving five references: one HTA report (from Ontario) 61 and four papers. [62][63][64][65] A summary of the included studies is provided in Table 13 with a quality checklist based on Drummond et al 66 provided in Table 14.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the remaining 29 titles, the full papers were screened, which led us to exclude another 24, leaving five references: one HTA report (from Ontario) 61 and four papers. [62][63][64][65] A summary of the included studies is provided in Table 13 with a quality checklist based on Drummond et al 66 provided in Table 14.…”
Section: Resultsmentioning
confidence: 99%
“…The review of economic analyses of different methods for KRAS mutation testing to decide between standard chemotherapy and cetuximab in combination with standard chemotherapy in adults with mCRC found four full papers [62][63][64][65] and one HTA report. 61 Based on all of these publications it can be said that, in general, although KRAS testing is obviously a more cost-effective option than administering cetuximab to all patients, the ICER of KRAS testing and treating only patients with KRAS wild-type tumours with cetuximab compared with treating all patients with standard chemotherapy alone seems rather high.…”
Section: Cost-effectivenessmentioning
confidence: 99%
“…Second, a more appropriate treatment selection helps avoiding useless toxicities and may studies published between 2000 and 2013 56 have both suggested. The evidence, however, remains controversial and extensively debated 57,58 . Although reasonable, if the addition of NRAS testing may increment the cost-effectiveness of the use of EGFR-I is currently unproven.…”
Section: All Authors Contributed To Conception and Design Manuscriptmentioning
confidence: 99%
“…According to a study screening for KRAS and BRAF mutations can reduce the cost of anti-EGFR treatment for metastatic CRC but with a very small reduction in overall survival (Behl et al 2012 ). Metastatic CRC patients whose tumors harbor mutations in KRAS (and to a lesser extent, in BRAF) are unlikely to respond to costly anti-EGFR therapies.…”
Section: Cost-benefi T Analysis Of Kras and Braf Screening In Crcmentioning
confidence: 99%